MATA PENCAHARIAN DAN KEARIFAN EKONOMI MASYARAKAT BADUY: MENJAGA TRADISI DI TENGAH PERUBAHAN ZAMAN - Sukaesih; Sapriya; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy community is an indigenous group known for their simple way of life and strong adherence to tradition amidst the waves of modernization. This study aims to understand how the Baduy people sustain their livelihood systems and economic wisdom while adapting to changing times without losing their cultural identity. This research employs a qualitative approach with descriptive methods. Data were collected through in-depth interviews with community leaders and members, direct observation of daily activities, and a review of related literature. The findings reveal that the Baduy people rely on activities such as slash-and-burn farming, gardening, and traditional handicraft-making, all conducted with sustainability principles and respect for nature. Their economic wisdom is reflected in a modest lifestyle, bartering practices, and minimal reliance on money. However, external influences, such as trade and tourism, are beginning to impact their community. In conclusion, the Baduy community has successfully preserved their traditions in their livelihood and economic systems while gradually adapting to change. This study highlights the importance of balancing modernization with cultural preservation as a key to sustaining their identity.